KEKERASAN BERBASIS GENDER ONLINE DALAM INTERAKSI DI MEDIA SOSIAL (Lembaga Penerbitan Universitas Esa Unggul, 2022)
The development of technology that underlies the emergence of various new online media platforms as a comprehensive communication medium. Social media as one of the new media platforms has become a mainstay medium for the community to meet their needs. The increasing number of social media users also adds to the new problems that arise in cyberspace, one of which is Online Gender-Based Violence (KBGO). Sexual violence is now easier to do through social media. There are no rules strong enough to prevent KBGO being one of the reasons such violence can occur. In addition, new trends on social media also support KBGO actors. This study aims to describe and analyze the KBGO phenomenon on social media. In this study, the researcher used a qualitative descriptive method to explain in depth the conditions of using social media and the KBGO phenomenon that occurred within the scope of social media. In addition, researchers also use literature studies as a method to collect references and references that are in accordance with the problem and research objectives.